PEMBERANGKATAN PENGANTIN YANG MEMAKAI PAKAIAN HAJI MENURUT HUKUM ISLAM - MISBAH MRD (Yurisprudentia: Jurnal Hukum Ekonomi, 2022)
This research is motivated by the customs of the Mandailing Natal community regarding the departure of the bride to the groom's house, in this case, the departing bride and groom always wear hajj clothes. This study is also to find out how the perception of the Mandailing Natal community about the departure of the bride and groom who wears hajj clothes according to Islamic law. This research is classified as field research, which uses a number of data collection models, including observation, in-depth interviews, and documentation methods. Seeing from some of the perceptions of the Mandailing Natal community about the Hajj clothes worn by the bride and groom as a prayer for the good of the bride and groom in their marriage, one of the perceptions expressed by the Mandailing Natal community is as follows: Baitullah (Mecca) to perform the Hajj. 2. In addition, the community also uses this dress as a prayer for the formation of the sakinah mawaddah warohmah family. The bride and groom who are sent to wear this hajj dress will forever embrace and hold fast to the religion of Islam, and have common sense even though there will be many trials in the household. 3. The white robe worn by the bride is as holiness, cleanliness and purity, this marriage which symbolizes purity and purity will be a good start for the bride and groom who will build a sakinah mawaddah warahmah family filled with pure, clean and pure love and the turban worn by the bride and groom man is the one symbolizing modesty. 4. The hajj dress is a symbol of the unity of the Muslim ummah. And this signifies their marriage is fortified with symbols of Islamic belief and faith. In the author's opinion, this perception builds benefit for the Mandailing Natal community and does not violate Islamic law at all, nor is it to erode bridal customs in Mandailing but to promote Islamic values within the community itself.